2022
DOI: 10.3390/ani12091130
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Tannin Extracts as Additives in Semen Destined for Cryopreservation: A Review

Abstract: Cryopreservation and storage of semen for artificial insemination (AI) result in excessive accumulation of reactive oxygen species (ROS). This leads to a shortened life span and reduced motility of spermatozoa post-thawing, with consequent impairment of their function. However, certain levels of ROS are essential to facilitate the capacitation of spermatozoa required for successful fertilisation. Tannins, as well-known antioxidant compounds, may act as ROS binders/acceptors/scavengers to inhibit the damaging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…For instance, Onyejike et al [ 19 ] reported that the herbal mixture contains tannins, saponins and flavonoids, and these plant chemicals are known to impact spermatogenesis. A typical example is tannins extracted from Z. officinale (a plant composition of the product) which have been reported to increase sperm parameters [ 20 ]. Despite the recorded significant increase in total sperm cell count of exposed male rats, the significant decrease in actively motile sperm cells, normal morphology as well as increase in non-motile sperm cells might indicate adverse exposure-associated effects of the polyherbal mixture.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Onyejike et al [ 19 ] reported that the herbal mixture contains tannins, saponins and flavonoids, and these plant chemicals are known to impact spermatogenesis. A typical example is tannins extracted from Z. officinale (a plant composition of the product) which have been reported to increase sperm parameters [ 20 ]. Despite the recorded significant increase in total sperm cell count of exposed male rats, the significant decrease in actively motile sperm cells, normal morphology as well as increase in non-motile sperm cells might indicate adverse exposure-associated effects of the polyherbal mixture.…”
Section: Discussionmentioning
confidence: 99%
“…Tannins are a diverse range of large-molecular-weight, watersoluble chemicals found naturally in various fruits, grains, and vegetables [193]. Tannins, potent antioxidant substances, serve as scavengers preventing harmful ROS effects [194]. Therefore, the compounds belonging to the tannin class with anti-NAFLD characteristics are enlisted in this section and outlined in ▶ Fig.…”
Section: Tanninsmentioning
confidence: 99%
“…Indicate protection of tannin-containing buffers from potential and active MYE during freezing and storage processes. The results of a study by Liman et al (2022) stated that tannins and their derivatives have natural protective properties that have the potential to improve the viability of sperm cells after freezing. Standar semen beku yang disyaratkan oleh SNI 4869-1:2021, motilitas sperma PTM > 40%.…”
Section: Ptm Sperma Dan Recovery Ratementioning
confidence: 99%